Adsorption of U(VI) ions using functionalized sago hampas : kinetics, isotherms, and thermodynamics studies - Wee, Boon Siong; Muhammade Firdaus, Maligan; Chin, Suk Fun; Md Suhaimi, Elias; Naoki, Shirai (Springer Nature, 2024)
Raw sago hampas (RSH) was grafted with oxygen-containing functional group through a functionalization process to form esterified sago hampas (ESH) for U(VI) adsorption and evaluated using adsorption kinetics, isotherm, and thermodynamics studies. Adsorption kinetics studies show that both adsorbents follow pseudo-second-order model while isotherm studies conclude that both adsorption processes fitted Sips isotherm model. Thermodynamic studies indicate both adsorption processes exhibited by the RSH and ESH were endothermic but spontaneous and non-spontaneous respectively. Strongs acids are tested to be the best desorption agents to release U(VI) from surfaces’ of RSH and ESH.